2013 Kansas performance tests with grain sorghum hybrids - Lingenfelser, Jane (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
Grain Sorghum Performance Tests, conducted annually by the Kansas Agricultural Experiment Station, provide farmers, extension workers, and seed industry personnel with unbiased agronomic information on many of the grain sorghum hybrids marketed in the state. Because entry selection and location are voluntary, not all hybrids grown in the state are included in tests, and the same group of hybrids is not grown at all test locations. Contributors Main Station, Manhattan Jane Lingenfelser, Assistant Agronomist (Senior Author) Doug Jardine, Extension Plant Pathologist Jeff Whitworth, Extension Entomologist Mary Knapp, KSU Weather Data Librarian Edward O. Quigley, Agricultural Technician Experiment Fields Eric Adee, Topeka Gary Cramer Hutchinson James Kimball, Ottawa Wendell Lilyhorn, Hutchinson Randall Nelson, Scandia Keith Thompson, Hutchinson Research Centers Wayne Aschwege, Hays Patrick Evans, Colby Kelly Kusel, Parsons Alan Schlegel, Tribune Monty Spangler, Garden City Cooperators Scott Chapman, Beloit Clayton Short, Assaria
Keywords: Kansas; Sorghum; Yield; Environmental factors